Penguatan eksistensi kota kreatif melalui inovasi desain kamuflase menara BTS berbasis zonasi wilayah - Nor Jayadi; Rahmawan Dwi Prasetya (Institut Seni Indonesia Yogyakarta, 2018)
This paper discusses an effort to maintain and strengthen the existence of Yogyakarta City as a creative city through the innovation of communication infrastructure in the form of BTS (Base Transceiver Station) tower by offering the idea of camouflage design of BTS tower based zonation area that has been determined in Yogyakarta City Local Regulation No. 1 of 2015 about Spatial Detail Plan and Zoning Regulation of Yogyakarta City 2015 - 2035. Besides being driven by the importance of communication aspect which is one of important elements in creative city, the design innovation is also expected to show the concern of all stakeholders about the importance of harmonization and aesthetics in a city area. Key words: BTS tower, camouflage, creative city